Formalización de una teoría de la mentalidad - Fernán Ulate Montero (Revista de Matemática: Teoría y Aplicaciones, 2009)
We introduce a model based in Game Theory, and those used primarily in biology (evolutionary games) to understand history. We are interested in use the model to understand the last years of the colony of Costa Rica. We proved several mathematical results. Keywords: Game theory, Nash equilibrium, evolution, cultural change, history.